2016
DOI: 10.1186/s40064-016-3589-z
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about and sources of smoking-related knowledge, and influencing factors among male urban secondary school students in Chongqing, China

Abstract: ObjectivesThis study examined smoking-related knowledge, sources of smoking-related knowledge and its influencing factor among male urban secondary school students.MethodsWe conducted a cross-sectional survey, using a self-administered questionnaire, among 1297 male secondary school students in municipal areas of Chongqing, China.ResultsNon-smokers had a better knowledge of smoking hazards than smokers. Less than 20% of students knew that smoking can cause heart disease, peptic ulcer, and cerebral stroke. Sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
10
6
1
Order By: Relevance
“…Adolescents tend to observe the short-term impact of smoking and therefore adopt the behavior because there is no immediate effect on health, indicating the inadequacy of the information available to them about the dangers. Furthermore, this study is in line with previous studies, which reported that a number of secondary school students in urban areas lack specific knowledge about smoking-related diseases [37], and also other studies that showed the main motivation is to be social.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Adolescents tend to observe the short-term impact of smoking and therefore adopt the behavior because there is no immediate effect on health, indicating the inadequacy of the information available to them about the dangers. Furthermore, this study is in line with previous studies, which reported that a number of secondary school students in urban areas lack specific knowledge about smoking-related diseases [37], and also other studies that showed the main motivation is to be social.…”
Section: Discussionsupporting
confidence: 92%
“…However, some teenagers in this study viewed smoking as makruh, which means it is allowed, although it is better to not smoke. Furthermore, this result agrees with a previous study, which stated its permissibility, whereby Muslim smokers perceive the behavior as acceptable in Islam -hence, Makruh -although, if it is too much, it could be haram [37]. This awareness fuels the desire to smoke and the desire to continue to do so among teenagers, eventually creating dependence.…”
Section: Discussionsupporting
confidence: 91%
“…However, some teenagers in this study view smoking as Makruh, which means it is allowed, although it is better to not. Furthermore, this result agrees with the previous study, which stated its permissibility, where Muslim smokers perceive the behavior as acceptable in Islam -hence, Makruh, although, if it is too much, it could be haram [36]. This awareness propels the desire to smoke among teenagers and the continuity to do so, eventually creating dependence.…”
Section: Discussionsupporting
confidence: 91%
“…Adolescents tend to observe the short-term impact of smoking and therefore adopt the behavior because there is no immediate effect on health, indicating the inadequacy of the information available to them about the dangers. Furthermore, this study is in line with previous studies, which reported that a number of secondary school students in urban areas lack speci c knowledge about smoking-related diseases [37], and other studies that showed the main motivation is to be social [38]. The dangers of tobacco are seen to be low, and an independent risk factor is a perception that friends and other students take substances and drink alcohol [39].…”
Section: Discussionsupporting
confidence: 91%